THE INFLUENCE OF E-COMMERCE, ACCOUNTING INFORMATION SYSTEMS, AND CAPITAL AVAILABILITY ON ENTREPRENEURIAL DECISION MAKING WITH SELF EFFICACY AS A MODERATING VARIABLE - Khoirunisa Hardhianti; Hadiah Fitriyah (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of e-commerce, accounting information systems, and business capital on entrepreneurial interest, focusing on how these factors contribute to decision-making and business development. Method: A quantitative approach is applied to examine the relationships among variables influencing entrepreneurial intentions, emphasizing the role of technology, information systems, and financial resources in fostering entrepreneurship. Results: The findings indicate that e-commerce significantly enhances entrepreneurial interest by simplifying business transactions and expanding market access. Accounting information systems provide relevant, reliable, and easily understood financial information that supports strategic decision-making, while sufficient business capital strengthens entrepreneurs’ ability to initiate and sustain ventures. Limited access to capital, however, remains a key barrier that often discourages potential entrepreneurs from pursuing business opportunities. Novelty: This study integrates technological, informational, and financial perspectives to explain entrepreneurial interest, offering new insights into how digital commerce and accounting systems jointly stimulate entrepreneurship in the modern economic landscape.